Malaysian ESL undergraduates’ learning experience and performance in a massive open online course on writing - Hasan, Md. Masudul (2016)
Massive open online courses (MOOCs) have revolutionized e-learning through innovating and improvising new pedagogical features and instructional tools.Despite the conceptual and terminological confusion, MOOCs have been well received by society, as evidenced by the enrolment numbers, course statistics, and feedback from students and teachers. Many well-known institutions such as Stanford University, MIT, and Harvard University have embraced the MOOC format to offer courses in various disciplines including English language. The present study has examined a class of ESL undergraduates’ learning experience and performance in a writing MOOC. Several research questions were designed to investigate how the participants perceive a writing MOOC, what they like about it, how they learn it, and what motivate them to learn. Moreover, the participants’ level of engagement and their purposes of interaction in the writing MOOC were examined. In addition, the reliability and validity of the participants’ peer assessment comments were discussed.A case study approach involving both qualitative and quantitative data collection methods was applied. The participants, comprising 48 ESL undergraduates, were taken from an intact class at a Malaysian public university. They were instructed to register and enrol in a writing course named A Beginners Guide to Writing in English for University Study. Data were collected through various means, i.e. (a) questionnaire, (b) reflection essays, (c) interview, (d) forum posts, (e) MOOC records, and (f) peer assessment comments.Findings obtained from the questionnaires and reflection essays show that most of the participants expressed positive attitudes towards learning in MOOC. They valued the MOOC instructional features and tools and showed strong satisfaction in learning academic writing. This study has also documented a number of factors that motivate students to enrol and complete MOOCs such as the quality of instructional pedagogy, self-directness, courses offered by a prestigious university, new knowledge, certification, and MOOC as edutainment. The findings associated with low retention rates are high workload, challenging course content, lack of time, lack of pressure, and lack of support from the course instructor. Participants’ level of engagement in terms of completing the required tasks in writing MOOC was found to be impressive. However, there was limited interaction in the forum between the peers and course instructor. The forum was used mainly for answering instructor’s questions, publishing essays, commenting on peers’ posts, and evaluating peers’ essays. Finally, the peer assessment comments collected suggest high level of agreement between student-assigned comments and feedback, and instructorassigned comments and feedback.This study has contributed new empirical data related to the application of a new innovation of e-learning in the form of writing MOOC. The findings also contribute to a better understanding of the nature of learning and participation in the MOOC from the perspective of ESL students.